2009
DOI: 10.5539/gjhs.v1n2p50
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Consumer Satisfaction of Health Care in Ghana: Does Choice of Health Care Provider Matter?

Abstract: A modern health system which provides high quality care has trickle-down effect on the quality of life of the individual citizens and the overall economic development of the country. One method which is applicable to the measurement of quality of health care is consumers' ratings of the services provided. This paper investigated the overall level of satisfaction associated with the choice of a health care provider. Parents whose children (aged-under five) fell sick four weeks prior to the survey and had sought… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 30 publications
4
27
1
1
Order By: Relevance
“…11 In Mozambique no recent studies on service satisfaction could be found; however, research completed in other areas of sub-Saharan Africa confirms the importance of waiting time, friendliness of staff, women's education, and distance/proximity to health facilities as the main determinants of client satisfaction. [12][13][14] The aim of this study was to assess the satisfaction and associated factors among women attending FP services at public health facilities in Mozambique.…”
Section: Introductionmentioning
confidence: 99%
“…11 In Mozambique no recent studies on service satisfaction could be found; however, research completed in other areas of sub-Saharan Africa confirms the importance of waiting time, friendliness of staff, women's education, and distance/proximity to health facilities as the main determinants of client satisfaction. [12][13][14] The aim of this study was to assess the satisfaction and associated factors among women attending FP services at public health facilities in Mozambique.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies suggest that increases in access to and use of primary care services are associated with a rise in user satisfaction levels [28]. Similarly, having a choice of provider is also associated with increased satisfaction with health services [16,23]. …”
Section: Discussionmentioning
confidence: 99%
“…It has become one of the most used criteria for establishing health care quality [2–4]. Previous studies argue that satisfied customers tend to develop trusting relationship with healthcare providers and to reveal higher levels of cooperation, which determine higher health outcomes [5, 6].…”
Section: Introductionmentioning
confidence: 99%